Detection and isolation of typical gut indigenous bacteria in mice fed corn starch, bread flour or whole wheat flour. Issue 1 (20th March 2022) - Takei, Natsumi; Kuda, Takashi; Handa, Natsumi; Takahashi, Hajime; Kimura, Bon
Abstract: Whole wheat flour (WWF) is regarded to have preventive effects on life‐style diseases. Detection, identification and isolation of WWF‐responsive gut indigenous bacteria (RIB) should reveal the gut microbiota‐mediated properties of WWF. To confirm the existence and roles of bread flour (BF)‐ and WWF‐RIB, Institute of Cancer Research mice were fed a diet containing corn starch (CS), BF or WWF as the starch source for 14 days. WWF increased in defecation. BF‐ and WWF‐RIB were detected using 16S rRNA(V4) gene amplicon sequencing. Amplicon sequence variants (ASVs) of Lactobacillus johnsonii ‐like bacteria in both BF and WWF groups (respective relative abundance: 9.3% and 9.4%) were higher than those in the CS group (0.5%). While Lactobacillus intestinalis ‐ and Limosilactobacillus reuteri ‐like bacteria ASVs were high in the WWF group (0.8% and 1.7%, respectively), these were not detected in the CS group. In contrast, ASVs of Blautia ‐, Clostridium saudiense/disporicum ‐, Lactobacillus murinus ‐, Muribaculaceae ‐, Phocaeicola vulgatus ‐ and Bifidobacterium pseudolongum ‐like bacteria in CS‐fed mice were higher than those in the other mice. Among these BF‐ and WWF‐RIB, L. johnsonii and L. reuteri could be isolated. Further studies on the isolation of the RIB from the human gut are required. Abstract : Corn starch (CS), Bread flour and whole wheat flour (WWF) were fed to Institute of Cancer Research mice. Lactobacillus johnsonii‐ Limosilactobacillus reuteri ‐ and Lactobacillus intestinalis ‐like were high in mice fed WWF rather than CS. Among these WWF‐responsive gut commensals, L. johnsonii and L. reuteri could be isolated.